Electromechanical Properties of Polymer Electrolyte‐Based Stretchable Supercapacitors. Issue 3 (17th September 2013) - Cole, Daniel P.; Reddy, Arava Leela Mohana; Hahm, Myung Gwan; McCotter, Ryan; Hart, Amelia H. C.; Vajtai, Robert; Ajayan, Pulickel M.; Karna, Shashi P.; Bundy, Mark L.
<x xml:space="preserve">Abstract</x> Aligned carbon nanotube (CNT) forests filled with a dehydrated polymer electrolyte are used to fabricate flexible solid state supercapacitors (SSCs) for multifunctional structural‐electronic applications. Local stiffness measurements on the composite electrodes determined through nanoindentation showed an 80% increase over the neat solid polymer electrolyte matrix. Electrochemical properties are monitored as a function of average tensile strain in the SSCs. Galvanostatic charge‐discharge tests with in situ microtensile testing on SSCs are used to show a 10% increase in the specific capacitance through the elastic region of the composite. The increase in capacitance is partly attributed to the enhanced double layer interaction that results from the partial alignment of the polymer electrolyte chains at the electrode‐electrolyte interface. When soaked in 1 m sulfuric acid, the specific capacitance of the CNT‐polymer electrolyte reached approximately 72 F g–1 at 60 °C.